Tracking of Maternal Diet from Pregnancy to Postpregnancy: A Systematic Review of Observational Studies. Issue 8 (15th July 2020) - Lee, Yu Qi; Loh, Jason; Ang, Rebekah Su Ern; Chong, Mary Foong-Fong
ABSTRACT: We systematically reviewed studies to examine changes in women's diets from pregnancy to the postpregnancy period and sought to understand the characteristics of women making these changes. From a search of 4 databases and up to November 2019, 17 studies met our inclusion criteria. They reported changes in various dietary aspects. Mixed findings were reported for changes in energy and micronutrient intakes. Most studies reported significant decreases in fruit and vegetable consumption, diet quality, and adherence to a healthier dietary pattern during the transition from pregnancy to postpregnancy, whereas increases in discretionary food and fat intakes were observed. Women with lower education level, lower income, and/or who worked full-time tended to have poorer dietary behaviors postpregnancy. Further research, with better aligned dietary measurement time points during pregnancy and postpartum and standardization of dietary assessment tools, is needed for future studies to be comparable. The systematic review protocol was registered in the PROSPERO International Prospective Register of Systematic Reviews as CRD42020158033.